Disorder and Confinement Effects to Tune the Optical Properties of Amino Acid Doped Cu2O Crystals. (24th April 2022) - Kurashvili, Mariam; Polishchuk, Iryna; Lang, Arad; Strohmair, Simone; Richter, Alexander F.; Rieger, Sebastian; Debnath, Tushar; Pokroy, Boaz; Feldmann, Jochen
Abstract: Biominerals are organic–inorganic nanocomposites exhibiting remarkable properties due to their unique configuration. Using optical spectroscopy and theoretical modeling, it is shown that the optical properties of a model bioinspired system, an inorganic semiconductor host (Cu2 O) grown in the presence of amino acids (AAs), are strongly influenced by the latter. The absorption and photoluminescence excitation spectra of Cu2 O‐AAs blue‐shift with growing AA content, indicating band gap widening. This is attributed to the void‐induced quantum confinement effects. Surprisingly, no such shift occurs in the emission spectra. The theoretical model, assuming an inhomogeneous AA distribution within Cu2 O‐AAs due to compositional disorder, explains the deviating behavior of the photoluminescence. The model predicts that the potential causing the confinement effects becomes a function of the local AA density. It results in a Gaussian band gap distribution that shapes the optical properties of Cu2 O‐AAs. Imitating and harnessing the process of biomineralization can pave the way toward new functional materials. Abstract : The incorporation of amino acids (AA) in Cu2 O leads to band gap opening, attributed to confinement effects. However, their emission spectra are largely unaffected. The theoretical model assumes an inhomogeneous AA arrangement within Cu2 O. Consequently, the potential causing confinement effects becomes a function of the local AA density, resulting in a Gaussian band gap distribution that reflects the observations.